Comparative characteristics of the genetic structure of the Syrian cattle breed compared to Holstein and Aberdeen-Angus breeds - Alsalh, Mohammad Almohammad; Bakai, Anatoly; Feyzullaev, Feyzullah Ramazanovich; Bakai, Ferdaus Rafailovna; Lepekhina, Tatyana Viktorovna; Mkrtchyan, Gayane; Krovikova, Anna; Mekhtieva, Karina; Alyaseen, Ousama Alhammoud (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: The objective of this study was to perform a comparative analysis of allelic diversity to reveal population-genetic characteristics of animal breeds, namely Shami (SH), Holstein (HLS), and Aberdeen-Angus (A-A). Materials and Methods: The genetic materials of SH breed animals represented by wool with hair follicles were collected from 39 SH heads in Syria. Also, genetic materials of HLS breed of American selection (n = 55, HLS) and bulls and cows of A-A breed bred at breeding enterprises in Russia (n = 30, A-A) were collected. Genetic differences between the cattle groups were studied using 11 microsatellite markers. Results: The cattle breed in Syria was characterized by high genetic diversity, 107 alleles, while the average number of alleles per microsatellite locus was 9.23, which is significantly higher than that in the animals of HLS (6.18) and A-A (5.00). When analyzing the genetic equilibrium for individual locus in SH breed, a deviation from equilibrium at four loci was revealed: TGLA227, SPS115, TGLA122, and ETH225; at one locus in HLS breed: SPS115, for A-A breed: at two loci, i.e., TGLA122 and ETH225. When assessing the level of genetic consolidation, a deficiency of heterozygotes was observed in two of the three studied breeds: 4.8% for SH and 8.0% for A-A. A slight excess of heterozygotes was found in the HLS breed at the level of 0.2%. The average comparative measurement of genetic variation in different populations value for 11 loci for all breeds was 0.069, which indicates that 93.1% of the total variability is due to the intra-breed diversity, and only 6.9% is due to the differences between breeds. Conclusion: The analysis of the animals belonging to their breed has shown a 100% genetic consolidation and the compliance of individual animals with the respective breeds. The study of genetic distances, adjusted for small samples, revealed the smallest genetic distance between the SH breed and HLS breed, equaling 0.107. The A-A breed, which has its separate origin and has never been imported into the Syrian Arab Republic, adjoins this cluster as an independent branch. Microsatellites can be used as an essential criterion for assessing the population-genetic characteristics of groups of cattle of various breeds (degree of polymorphism, level of heterozygosity, fixation indices, genetic group membership). J. Adv. Vet. Anim. Res., 8(2): 339-345, June 2021